Discourse in Mass Media: A Study of Critical Analysis Research Agenda - Putri, Ade Gustia (English Education:Journal of English Teaching and Research, 2018)
This article tries to review several main topics in research approaches on texts of mass media from a perspective of discourse analytical. It tries to sum up that multidisciplinary of Critical Discourse Analysis approach to research on discourse of mass media rescue tell hidden socio-political problems and agenda in several areas of language as social practice. The Examples of definite research of CDA on mass media discourse are revised in terms of subjects of seeming popular and interest among practitioners such as language of globalization and neo-capitalism, racist discourse in news reporting and war news reporting. KEYWORD: Critical Discourse Analysis (CDA), Critical Discourse Studies, Mass Media Discourse, Media Text Analysis, Media Research Agenda.